Procedure for assessing the territorial innovation potential in the context of national economic interests - Zinchenko, Olha; Apalkova, Viktoriia; Mylnichenko, Serhii; Rudenko, Oksana; Prygodiuk, Olena (Eastern-European Journal of Enterprise Technologies, 2023)
Under the conditions of a gradual transition to the knowledge economy, the system of management of innovative development of territories is actualized in the context of the realization of their economic interests, which is the object of this study. The authors of this paper proceed from the fact that sustainable innovative development is possible subject to the activation of the innovative potential of the territory. This work solves the task of a comprehensive assessment of innovation potential from the standpoint of national economic interests. As a result of the study, a methodology for assessing the innovative potential of the region was proposed from the standpoint of ensuring the development of innovations, promoting the activity of innovation, guaranteeing its effectiveness and safety. The methodology differs from existing ones in that it takes into account such components as "innovative security" and "innovative support" of the territory. The methodology was verified using the example of economic regions. The influence of innovation potential on such indicators of realization of national economic interests as gross regional product and real disposable incomes of the population was revealed. Thus, the asymptotic significance of the ANOVA test in establishing the link between innovation potential and gross product is 0.005, and between innovation potential and income of the population – 0.00019. This testifies to the constancy of relations and confirms the hypothesis of the possibility to regulate the processes of realization of the national economic interests of the state through the impact on the innovative potential of its territories. The feature and advantage of the approach is a comprehensive assessment of the innovation potential and the ability to establish not only its condition but also the prospects for further activation. The results of the study can be useful for the system of state and regional management as they justify the directions of innovation policy formation